I non luoghi di Julio Cortázar - Silvestri, Laura (Rassegna Iberistica, 2016)
Read in light of Marc Augé’s «non places theory», Julio Cortázar’s narrations show how the unlimited technological development of Postmodernity lead people to allienation from themselves, their needs and feelings. In addition to that, they trigger a reflection about the dangers embedded in a passive way of living in the world, which, by making people used to the pre-established schemes, and hinder the possibility to imagine life in a different way.